PENGARUH DEBT DEFAULT DAN FINANCIAL DISTRESS TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Putri, Fadhilla Ananda; Astuti, Tutut Dewi (Universitas Muhammadiyah Palembang, 2023)
An auditor's opinion that ensures a business's ability to continue operating is known as a business continuity audit opinion. A company is granted going concern status depending on several factors, including the company's financial difficulties and its inability to fulfill its obligations. This research aims to find out whether there is a positive potential for financial distress and debt default on the ability to provide a business continuity audit opinion in the manufacturing industry listed on the IDX in 2021–2022. Using a purposive sampling technique, a sample of 104 manufacturing companies was obtained. Independent auditor reports and company annual reports are the data sources in this research. The logistic regression model is used to analyze the relationship between variables. The results of the research test state that providing a business continuity audit opinion is not affected by financial distress and debt default.